Hybrid Solar Cells: Efficient Perovskite Hybrid Solar Cells via Ionomer Interfacial Engineering (Adv. Funct. Mater. 44/2015). (23rd November 2015) - Wang, Kai; Liu, Chang; Yi, Chao; Chen, Long; Zhu, Jiahua; Weiss, R. A.; Gong, Xiong
Abstract : On page 6875, R. A. Weiss, X. Gong, and co‐workers re‐engineer the interface between the perovskite active layer and the electron‐extraction layer in perovskite hybrid solar cells, using an ultrathin layer of a highly conductive ionomer. The boosted performance of the resulting solar cells is attributed to the reduction in the charge carrier recombination and leakage current, as well as more efficient charge carrier collection.